Need a break? The locomotor and tackle pacing profile and loads of women`s rugby league match-play following various between-match turnaround durations - Cummins, C.; Charlton, G.; Buxton, S.; Shorter, K.; Paul, D.; Murphy, A. (Science and Medicine in Football, 2024)
Objectives: The study investigated the locomotor and tackle pacing profile and loads of female rugby league players following various between-match turnaround durations. Specifically, the study examined the (1) pacing of locomotor and tackle loads across the time-course of a match and; (2) whole-match and peak locomotor and tackle loads of match-play. Methods: Microtechnology data were collected from elite female rugby league players (n = 172) representing all National Rugby League Women`s teams (n = 6 teams) across two seasons. Players were categorised into backs, adjustables, forwards or interchange players. Data was calculated for the whole-match (m), per minute (m.min-1) and peak (running: m.min-1; acceleration: m.s-2) locomotor and tackle loads (number and efficiency (%)) of match-play. The pacing as well as the locomotor and tackle loads of match-play were examined following short (=6 days), normal (7 days) or long (=8 days) turnarounds. Results: The pacing profile of playing positions varied across short, normal and long match turnarounds. Trivial to moderate differences existed in the whole-match, per minute and peak locomotor loads across match turnaround durations (effect size = 1.2). Conclusions: Following various between-match turnaround durations (i.e., short, normal and long match turnarounds), there were variations in the locomotor and tackle pacing profile and loads whereby, the pacing profile of positional groups was more affected than the load profile. The findings can be used in applied settings to guide the recovery strategies and training plans of female rugby league players to optimise performance and wellbeing across various match turnaround durations.